2019
DOI: 10.1038/s41598-019-51354-y
|View full text |Cite
|
Sign up to set email alerts
|

Computing on actin bundles network

Abstract: Actin filaments are conductive to ionic currents, mechanical and voltage solitons. These travelling localisations can be utilised to generate computing circuits from actin networks. The propagation of localisations on a single actin filament is experimentally unfeasible to control. Therefore, we consider excitation waves propagating on bundles of actin filaments. In computational experiments with a two-dimensional slice of an actin bundle network we show that by using an arbitrary arrangement of electrodes, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 67 publications
(80 reference statements)
0
27
0
Order By: Relevance
“…Later, we realized that it might be unrealistic to expect someone to initiate and record travelling localizations (solitons, impulses) on a single actin filament. Therefore, we developed a numerical model of spikes propagating on a network of actin filament bundles and demonstrated that such a network can implement Boolean gates [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Later, we realized that it might be unrealistic to expect someone to initiate and record travelling localizations (solitons, impulses) on a single actin filament. Therefore, we developed a numerical model of spikes propagating on a network of actin filament bundles and demonstrated that such a network can implement Boolean gates [33].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated how to discover logical gates on a two-dimensional slice of the actin bundle network by representing Boolean inputs and outputs as spikes of the network activity. In a previous paper [33], we demonstrated, using numerical integration of FitzHugh–Nagumo model, that a two-dimensional actin network realized k -ary Boolean functions G : {0, 1} k → {0, 1}, when k input electrodes and one output electrodes are employed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9. This is accompanied by distributions of gates discovered in experimental laboratory reservoir computing with slime mould Physarum polycephalum [34], succulent plant [11] and numerical modelling experiments on computing with protein verotoxin [2], actin bundles network [12], and actin monomer [3]. All the listed distributions have very similar structure with gates selecting one of the inputs in majority, followed by or gate, not-and an and-not gates.…”
Section: Distribution Of Boolean Gatesmentioning
confidence: 99%